2013
DOI: 10.5194/acp-13-2391-2013
|View full text |Cite
|
Sign up to set email alerts
|

Long term measurements of aerosol optical properties at a primary forest site in Amazonia

Abstract: A long term experiment was conducted in a primary forest area in Amazonia, with continuous in-situ measurements of aerosol optical properties between February 2008 and April 2011, comprising, to our knowledge, the longest database ever in the Amazon Basin. Two major classes of aerosol particles, with significantly different optical properties were identified: coarse mode predominant biogenic aerosols in the wet season (January–June), naturally released by the forest metabolism, and fine mode dominated biomass … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
144
3
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(174 citation statements)
references
References 75 publications
19
144
3
8
Order By: Relevance
“…Recent studies showed an increase of b abs from the wet to the dry season from 0.5 Mm −1 to 2.8 Mm −1 (factor 5.6) in the Amazon rain forest at 110 m a.s.l. (Rizzo et al, 2013). This is twice the increase of b abs compared to our observations of biomass burning in the savannah.…”
Section: Seasonal Cyclesupporting
confidence: 48%
See 1 more Smart Citation
“…Recent studies showed an increase of b abs from the wet to the dry season from 0.5 Mm −1 to 2.8 Mm −1 (factor 5.6) in the Amazon rain forest at 110 m a.s.l. (Rizzo et al, 2013). This is twice the increase of b abs compared to our observations of biomass burning in the savannah.…”
Section: Seasonal Cyclesupporting
confidence: 48%
“…Approximately 40 % of the total particulate mass which is released by deforestation activities in the Tropics originates from biomass burning in the Amazon region (Longo et al, 2009). In addition, long-range transport of biomass burning aerosol and dust from northern and tropical Africa to South America via the Atlantic was observed by foregoing studies (Edwards et al, 2006;Ansmann et al, 2009;Adams et al, 2012;Rizzo et al, 2013). We used HYSPLIT trajectories in combination with the MODIS Global Monthly Fire Location Product to detect possible source regions during the dry and wet season.…”
Section: Identification Of Source Regionsmentioning
confidence: 99%
“…Rizzo et al (2013), however, pointed out that this relationship is only evident for surface and volume mean diameters and was not clearly valid between å sca and count mean diameters. We obtained higher å sca values during the dry season (1.71 ± 0.24) compared to the wet season (1.29 ± 0.50) as shown in Fig.…”
Section: Overview Of Aerosol Optical Properties (2012 -2017)mentioning
confidence: 98%
“…3). To have a broader view on how this phenomenon affected the Amazon rain forest aerosol, we added scattering and absorption data from ZF2 published in Rizzo et al (2013) and extended with recent data to the current ATTO time series in Fig. 7a-b.…”
Section: El Niño Impact On Aerosol Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation